2024
DOI: 10.1051/0004-6361/202348321
|View full text |Cite
|
Sign up to set email alerts
|

Super-early JWST galaxies, outflows, and Lyαvisibility in the Epoch of Reionization

A. Ferrara

Abstract: The overabundance of super-early (redshift $z>10$) luminous ($M_ UV < -20$) blue galaxies detected by JWST has been explained as being due to negligible dust attenuation in these systems. We show that this model correctly reproduces the UV luminosity function at $z>10$ and the star formation rate (SFR) density evolution. The model also predicts, in agreement with data, that the cosmic specific SFR (sSFR) grows as $ sSFR $. At $z 10$, the cosmic sSFR crosses the critical value $ sSFR^ $, and approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 145 publications
1
3
0
Order By: Relevance
“…For instance, the feedback-free models of Dekel et al (2023) and Li et al (2023) agree with our z ∼ 12 observations for an efficiency of »  0.2 max . Models for the evolving number counts of high-redshift galaxies based on dust-free populations (e.g., Ferrara et al 2023) also predict an SFR density evolution to z ∼ 15 in agreement with our inferences, assuming all our candidates are really high-redshift sources (Ferrara 2024).…”
Section: Discussionsupporting
confidence: 84%
“…For instance, the feedback-free models of Dekel et al (2023) and Li et al (2023) agree with our z ∼ 12 observations for an efficiency of »  0.2 max . Models for the evolving number counts of high-redshift galaxies based on dust-free populations (e.g., Ferrara et al 2023) also predict an SFR density evolution to z ∼ 15 in agreement with our inferences, assuming all our candidates are really high-redshift sources (Ferrara 2024).…”
Section: Discussionsupporting
confidence: 84%
“…Evolving their model to higher redshifts, they naturally predict a slowing in the evolution of the UV luminosity function from z ∼ 9 to 11 due to significantly reduced attenuation in galaxies. This arises in their model owing to outflows driven by very high ("super-Eddington") specific SFRs, which can efficiently drive gas (and dust) out from these galaxies (Ferrara 2024). They discuss that this is supported by the data, as early results on the colors of z > 8 galaxies showed that they were fairly blue (e.g., Finkelstein et al 2022b;Topping et al 2022;Cullen et al 2023;Papovich et al 2023) and thus likely contained little dust.…”
Section: Change In Physical Processesmentioning
confidence: 95%
“…Alternatively, another possibility to reconcile our high cloudscale SFE values with relatively lower ò *,gal is that only a fraction of the gas in the galaxy participates in star formation in clouds. It is possible that the remaining gas is ejected in outflows by the feedback from older stellar populations, possibly explaining the dust-free nature of these galaxies (Ferrara 2024;Ferrara et al 2023;Fiore et al 2023), which is likely critical to simultaneously explain the observed UV luminosity functions and the blue UV continuum slopes (e.g., Cullen et al 2024)-although see Li et al (2023) for an alternative explanation of these findings. This possibility raises another effect of a top-heavy IMF that we cannot capture in our simulations: a top-heavy IMF 15 would lead to more energy and mass-loaded winds, potentially further decreasing ò *,gal , such that its combination with a top-heavy IMF could be consistent with the observations.…”
Section: Implications For Massive Galaxies At Cosmic Noonmentioning
confidence: 99%